2007
DOI: 10.1016/j.rmed.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The progressive effects of ageing on chemosensitivity in healthy subjects

Abstract: The aim of this study was to compare the central inspiratory drive (P(0.1)) response to hypoxia and hypercapnia between different age groups of elderly, nonsmoker, healthy subjects and young healthy controls. A random sample, proportionally stratified by age (65-69, 70-74, 75-79 and 80-84 yrs) from a sample of nonsmoker elderly subjects representative of a general population and 47 healthy subjects aged 20-40 were selected. Arterial blood gas, lung volumes, diffusing capacity, maximal respiratory pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
1
26
0
2
Order By: Relevance
“…The influence of ageing on ventilatory response to acute hypoxia has been scarcely studied in humans. The previous protocols compared young (20–40 years) with older (60–85 years) groups and always included a limited number of subjects, between 15 (Vovk et al 2004) and 112 (Garcia‐Rio et al 2007). Most of these studies used isocapnic hypoxia and all focused on response at rest.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of ageing on ventilatory response to acute hypoxia has been scarcely studied in humans. The previous protocols compared young (20–40 years) with older (60–85 years) groups and always included a limited number of subjects, between 15 (Vovk et al 2004) and 112 (Garcia‐Rio et al 2007). Most of these studies used isocapnic hypoxia and all focused on response at rest.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Lhuissier et al, 2012. Pokorski et al, 2004;Vovk et al, 2004;Paleczny et al, 2014) while some others found a reduced HVR in old persons (Kronenberg and Drage, 1973;Peterson et al, 1981;Serebrovskaya et al, 2000;Garcia-Rio et al, 2007). Chapman and Cherniack (1987) were the only authors to report an enhanced HVR in the elderly.…”
Section: Longitudinal Studymentioning
confidence: 98%
“…Although not a universal finding, aging has been associated with a decrease in the HVR in humans (17,26,38); however, the specific mechanisms by which this occurs remains unclear. Indeed, a brisk HVR would seem important in patients with lung disease to maintain oxygenation, particularly in situations where they may be exposed to acute hypoxic events.…”
mentioning
confidence: 99%